Grand Challenges in Comparative Tooth Biology. (13th June 2020) - Hulsey, C Darrin; Cohen, Karly E; Johanson, Zerina; Karagic, Nidal; Meyer, Axel; Miller, Craig T; Sadier, Alexa; Summers, Adam P; Fraser, Gareth J
Abstract: Teeth are a model system for integrating developmental genomics, functional morphology, and evolution. We are at the cusp of being able to address many open issues in comparative tooth biology and we outline several of these newly tractable and exciting research directions. Like never before, technological advances and methodological approaches are allowing us to investigate the developmental machinery of vertebrates and discover both conserved and excitingly novel mechanisms of diversification. Additionally, studies of the great diversity of soft tissues, replacement teeth, and non-trophic functions of teeth are providing new insights into dental diversity. Finally, we highlight several emerging model groups of organisms that are at the forefront of increasing our appreciation of the mechanisms underlying tooth diversification.